2021
DOI: 10.1128/msystems.01136-21
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SARS-CoV-2 RNA Persistence across Indoor Surface Materials Reveals Best Practices for Environmental Monitoring Programs

Abstract: Environmental monitoring is an important tool for public health surveillance, particularly in settings with low rates of diagnostic testing. Time between sampling public environments, such as hospitals or schools, and notifying stakeholders of the results should be minimal, allowing decisions to be made toward containing outbreaks of coronavirus disease 2019 (COVID-19).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…We estimated surface viral load, in viral genomic equivalents (GE’s), from Cq’s using published regression curves ( 17 ) and mapped resulting viral loads onto 3D renderings of each apartment. High-touch surfaces had the highest viral load across all apartments, followed by floor samples and then high-use objects (fridge, sinks, toilets, and beds) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We estimated surface viral load, in viral genomic equivalents (GE’s), from Cq’s using published regression curves ( 17 ) and mapped resulting viral loads onto 3D renderings of each apartment. High-touch surfaces had the highest viral load across all apartments, followed by floor samples and then high-use objects (fridge, sinks, toilets, and beds) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In all three apartments, the rate of detection was highest in the bedroom (72% on average vs 47% overall). We estimated surface viral load, in viral Genomic Equivalents (GE’s), from Cq’s using published regression curves ( 17 ) and mapped resulting viral loads onto 3D renderings of each apartment. High-touch surfaces, including handles and switches, had highest viral load across all apartments, followed by floor samples and then high-use objects (fridge, sinks, toilets, beds) ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have already demonstrated that viral signals from COVID-19 patients in indoor environments commonly accumulate on high-touch surfaces and the floors in front of features with high interaction times [8]. Additionally, SARS-CoV-2 RNA has been demonstrated to persist for up to a week on several indoor surface types [7, 10], making it difficult to understand exactly when an infected individual came into contact with a surface or if consecutive positives are from new deposition events. Thus, an effective post-sampling cleaning procedure needs to be established in order to increase temporal resolution and ensure that consecutive positives are from new infection events.…”
Section: Bodymentioning
confidence: 99%
“…To continue benchmarking proven environmental pipelines [7, 9, 11] and to account for potential interactions, we used a factorial study design covering two swabbing media (SDS, VTM), three cleaning solutions (BZK wipes, wet wipes, RNase Away) and three viral spike-in concentrations (High, Medium, Low). Each condition was performed in triplicate for a total of 54 cards.…”
Section: Bodymentioning
confidence: 99%